2003
DOI: 10.1085/jgp.200208777
|View full text |Cite
|
Sign up to set email alerts
|

Ion Fluxes in Giant Excised Cardiac Membrane Patches Detected and Quantified with Ion-selective Microelectrodes

Abstract: We have used ion-selective electrodes (ISEs) to quantify ion fluxes across giant membrane patches by measuring and simulating ion gradients on both membrane sides. Experimental conditions are selected with low concentrations of the ions detected on the membrane side being monitored. For detection from the cytoplasmic (bath) side, the patch pipette is oscillated laterally in front of an ISE. For detection on the extracellular (pipette) side, ISEs are fabricated from flexible quartz capillary tubing (tip diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Although these methods have not been used widely, they are well established and validated ( Smith and Trimarchi, 2001 ;Kang et al, 2003 ). We have analyzed our data in relation to two coupled dimer transport models that appear broadly consistent with our new data and data from the literature.…”
Section: Discussionsupporting
confidence: 57%
“…Although these methods have not been used widely, they are well established and validated ( Smith and Trimarchi, 2001 ;Kang et al, 2003 ). We have analyzed our data in relation to two coupled dimer transport models that appear broadly consistent with our new data and data from the literature.…”
Section: Discussionsupporting
confidence: 57%
“…2A) requires assuming that the oocyte has modest CA activity both on the extracellular surface and in the cytoplasm. However, this endogenous intracellular CA activity must be insensitive to EZA because both Lu et al (33) and we found that pretreating "Tris" oocytes with 400 M EZA has no effect on a CO 2 -induced (dpH i /dt) max (Fig. 4C vs. D, Fig.…”
Section: Table 4 Nominal Intrinsic Intracellular Buffering Power (␤)*mentioning
confidence: 51%
“…We pulled these pipettes from standard-wall borosilicate tubing (part no. G200F-4, 2.0 mm OD ϫ1.16 mm ID, Warner Instruments) and used a microforge to break off and fire polish the tips as one would for a giant-patch pipette (33). During experiments, we attach the pH S electrode to an ultra-fine computer-controlled micromanipulator with digital position display (model MPC-200 system, Sutter Instrument).…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%
“…Measurements of extrapipette and intrapipette ion gradients, and the physical principles and diffusion models, have been described (11). Briefly, extrapipette pH microelectrodes were mounted with sticky wax in a 1.3-mm-wide slit of a temperature-controlled recording chamber, and a fine, chlorided silver wire was then inserted into the back-filled electrolyte solution and connected to the probe of a high-input resistance (10 15 ⍀) electrometer (World Precision Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Here we describe an approach using pH microelectrodes during whole-cell patch clamp recording. Extracellular H ϩ gradients caused by H ϩ transport are detected by moving cells close to and away from a pH microelectrode in the presence of low buffer concentrations and measuring the H ϩ gradient with cancellation of electrode drift (9)(10)(11). Extensive manipulation of the cytoplasmic medium is possible by pipette perfusion, and H ϩ fluxes can be quantified by simulation of buffer diffusion.…”
mentioning
confidence: 99%